The Dimensionality of the Brief COPE Before and During the COVID-19 Pandemic. (March 2023) - Hanfstingl, Barbara; Gnambs, Timo; Fazekas, Christian; Gölly, Katharina Ingrid; Matzer, Franziska; Tikvić, Matias
The Brief COPE (Coping Orientation to Problems Experienced) is a frequently used questionnaire assessing 14 theoretically derived coping mechanisms, but psychometric research has suggested inconsistent results concerning its factor structure. The aim of this study was to investigate primary and secondary order factor structures of the Brief COPE during the COVID-19 pandemic by testing 11 different models by confirmatory factor analyses and to assess differences between sex, age groups, and relationship status. Altogether, 529 respondents from Austria and Germany participated in a web-based survey. Results supported the originally hypothesized 14-factor structure but did not support previously described higher-order structures. However, bass-ackwards analyses suggested systematic overlap between different factors, which might have contributed to different factor solutions in previous research. Measurement invariance across sex, age groups, and relationship status could be confirmed. Findings suggest that cultural and situational aspects as well as the functional level should be considered in research on theoretical framing of coping behavior.